Less Conservative State Feedback Design with Switched Controllers for TS Fuzzy Systems - Faria, Flávio A. [UNESP]; Elias, Leandro J.; Magossi, Rafael F. Q.; Carneiro, Diego S.; Oliveira, Vilma A. (Springer Nature, 2022)
In this work, relaxed conditions for parallel distributed compensation fuzzy controllers via state feedback are proposed. The LMI conditions are obtained exploring the properties induced by the sector nonlinearity approach and by partitioning the space generated by the first-order time derivative of the membership functions. A chattering free state-dependent switching law to ensure the asymptotic stabilization of the feedback system is obtained and the efficiency of the proposed results is supported by a numerical example.
Keywords: Right-hand side relaxation approach; State feedback design; Switched control; Takagi Sugeno fuzzy models